Unsung Land, Aspiring Nation Journeys in Bougainville - Peake, Gordon (Pacific Series, 2022)
In 2016, Gordon Peake answers a job advertisement for a role with the government of the Autonomous Region of Bougainville, a collection of islands on the eastern fringe of Papua New Guinea looking to strike out as a country of its own. In his day job he sees at first hand the challenges of trying to stand up new government systems. Away from the office he travels with former rebels, follows an anthropologist's ghost and visits landmarks from the region's conflict. In 2019, he witnesses joy and euphoria as the people of Bougainville vote in a referendum on their future. Out of these encounters emerges an unforgettable portrait of this potential nation-in-waiting. Blending narrative history, travelogue and personal reminiscences, Unsung Land, Aspiring Nation is an engaging memoir as well as an insightful meditation on the realities of nation-making and international development.